ADAPTATION AND STABILITY OF PROMISING WHEAT GENOTYPES FOR YIELD UNDER RAIN FED CONDITIONS OF HIGHLAND BALOCHISTAN - S. Khan; J. Khan; M. A. Khetran; A. Hanan; Amanullah; A. A. Kurd; N. S. Naseer; S. Jaffar (Journal of Animal and Plant Sciences, 2014)
Five wheat genotypes including local wheat as a check were tested for grain yield stability at three different locations under rained conditions during 2006-07 in highland of Balochistan, Pakistan. These genotypes were exposed to different soil type, soil fertility, moisture levels and temperature. The G × E interaction mean squares were non-significant for grain yield. The mean square due to pooled deviations were, however highly significant indicating significant difference among five genotypes for non liner response. The overall mean grain yield performance of genotypes across environments ranged from 1198 to 2203 kg/ha. The stability parameters indicated regression coefficient (bi) value ranging from 0.998 in AZRC-3 to 1.004 in local wheat cultivar. Cultivar AZRC-3 having by values close to unity with higher grain yield showed consistent performance under different environments and considered as stable and widely adopted. This cultivar also showed the ideal stable performance with regard to mean grain yield of 2203 kg/ha, regression coefficient value of 0.998 and dispersion value of 0.002 followed by cultivar AZRC-2 (1999 kg/ha) with regression coefficient value of 0.999 and dispersion value (0.000). Based on bi and S2d values cultivar AZRC-4 was found to be stable for specific adaptation in favorable environments and produced good yield with regression coefficient > 1.0. Whereas, cultivars AZRC-1, AZRC-2 and AZRC-3 having values close to unity with higher grain yield showed consistent performance over different environments and could be considered as stable and widely adapted.
Keywords: Moisture Stress; Wheat Adaptability; G x E Interaction